Application of Novel Methods for Mycotoxins Analysis - Ciasca, Biancamaria; Lattanzio, Veronica Maria Teresa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Crop contamination by mycotoxins is a global problem that poses significant economic burdens due to a number of factors, including the food/feed losses that are caused by reduced production rates; the resulting adverse effects on human and animal health and productivity; and the trade losses associated with the costs incurred by inspection, sampling, and analysis before and after shipments. In this scenario, the development of fit-for-purpose analytical methods for regulated and (re)-emerging mycotoxins continues to be a dynamic research area. Some of the current trends in this research area are presented in this book. The collected contributions address either the need for improved methods for mycotoxin detection addressed by new or incoming regulation (ergot alkaloids and Alternaria toxins) as well as methods for the detection of multiple mycotoxins. New approaches to enhance the performance of well-established methodologies, such as the enzyme-linked immunosorbent assay (ELISA) and fluorescence polarization immunoassays (FPIA), are also addressed.